Positive Psychology Interventions: How Do Alleviate the Symptoms of Depression? - A Literature Review - Aretha Ever Ulitua; Cindy Claudia Soen; Irena Monica Hardjasasmita; Naomi Soetikno (International Journal Labs, 2022)
Depression is a common psychological disorder that can influence a person’s feelings, way of thinking, and behavior in a negative way. Furthermore, biological factors, cognitive distortions, negative emotions, and cultural factors are accountable for the rise of depression. The etiology of depression is complex and no single cause can be accounted for. The prevalence of depression begins to rise in adolescence. From the perspective of positive psychology, depression can be viewed as a lack or excess of capabilities, strengths, and autonomy that make the individual focused on the negative side of the past. Positive Psychology Interventions (PPIs) were initially designed to increase the level of happiness. However, many studies have shown the effectiveness of PPIs to reduce the symptoms of depression. PPIs are based on the assumption that each individual has capacities for growth, fulfillment, and wellbeing. Thus, this study aims to investigate the effectiveness of PPIs on depression based on a literature review from the last three years as a research method. The overall results from this review are that PPIs can decrease depression symptoms, adolescents with depression have improvements in other characteristics, and even are in charge of preventing depression.